Vacuum freeze drying method of cordyceps militaris - SUN CUIHUAN; CHEN JIE; XU CHONG; CHEN LIYUAN; FENG HUA (2017)
The invention discloses a vacuum freeze drying method of cordyceps militaris. Glucose and citric acid are added into water, cordyceps militaris immersion liquid is prepared, the cordyceps militaris is soaked in the cordyceps militaris immersion liquid for 5 minutes to 10 minutes, shape fixing is carried out, after water filtering, the cordyceps militaris is flatly laid in a material plate, and is loaded into a material box, the pre-cooling temperature of the material reaches -40 DEG C to -50 DEG C, the temperature is kept for 2.0 hours to 2.5 hours, vacuum pumping is carried out, after the vacuum pressure is reduced to 50 Pa or below, temperature rise begins, vacuum pumping continues, equipment runs for 18 hours or above, the temperature of a material bin is 32 DEG C, then, dried cordyceps militaris is taken out, and frozen dried cordyceps militaris is obtained. The method has the beneficial effects that the cordyceps militaris is subject to vacuum freeze drying, the color of the finished product is golden an